The Effects of Populism on Muslim Minorities: How Politicians’ Distrust in Islam Affects Muslim Attitudes Towards Violence in the Netherlands? - Ertugrul Gokcekuyu (Nazhruna: Jurnal Pendidikan Islam, 2023)
Extreme right pronouncements concerning Muslim minorities in the Netherlands have been on the political agenda since the eighties of the last century. However, the intensity of extreme right pronouncements has increasingly been more negative creating a sphere of political distrust in politics, politicians and democracy. Specific verbal remarks made by Dutch politicians, time and again suggest a link between Muslims, Islam and violence. The central question in this article is whether Muslim inclination toward violence or a hard approach ‘physical if necessary’ can be predicted by the centrality of Islam together with the variable Dutch politicians’ negative remarks about Islam and Muslims. In this article, a model is hypothesized and constructed by way of logistic regression to predict the probability of inclination toward violence. The findings show that variables such as gender, discrimination, a theological belief that Islam forbids politics and the variable state intervention in religious affairs such as appointing a mufti (versus communal election) are good predictors of Muslim individuals’ inclination toward violence.